2008
DOI: 10.1016/j.ijrobp.2007.08.083
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Credentialing Institutions and Participants in Advanced Technology Multi-institutional Clinical Trials

Abstract: The Radiological Physics Center (RPC) has functioned continuously for 38 years to assure NCI and the cooperative groups that institutions participating in multi-institutional trials can be expected to deliver radiation treatments that are clinically comparable to those delivered by other institutions in the cooperative groups. To accomplish this, the RPC monitors the machine output, the dosimetry data utilized by the institutions, the calculation algorithms used for treatment planning, and the institutions' qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
103
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(104 citation statements)
references
References 16 publications
1
103
0
Order By: Relevance
“…Ratios of the PTV TLD doses for the other irradiations ranged from 0.95 to 0.98, and the percentage of points passing the gamma index ranged from 96% to 97%. Considering the first time pass rate of the RPC lung phantom is only 71%, (18) it represents a rigorous test for the FFF beam modeling and commissioning.…”
Section: Resultsmentioning
confidence: 99%
“…Ratios of the PTV TLD doses for the other irradiations ranged from 0.95 to 0.98, and the percentage of points passing the gamma index ranged from 96% to 97%. Considering the first time pass rate of the RPC lung phantom is only 71%, (18) it represents a rigorous test for the FFF beam modeling and commissioning.…”
Section: Resultsmentioning
confidence: 99%
“…While implementation of multi‐material 3D printed phantoms would be a further improvement, homogeneous phantoms are at present routinely used for many different types of radiation treatment QA. Examples include patient‐specific IMRT QA and accreditation procedures for clinical trials 15, 16…”
Section: Discussionmentioning
confidence: 99%
“…Such programmes should result in both improved robustness of the study results and improved quality of the radiation technique once implemented in routine practice. [15][16][17][18] RT protocol deviations should be minimized as they can have a major impact on the outcome of a study as demonstrated in the HeadSTART trial evaluating the role of tirapazamine in advanced head and neck cancer. 19 The participating centres were required to submit the diagnostic imaging and treatment plans for patients entered into the trial to a QA review committee by the end of the first week of RT.…”
Section: Discussionmentioning
confidence: 99%